Management of the monochorionic monoamniotic twin pregnancy: literature review and case report - Gil Guevara, Enrique (2022)
About a case presentation of a monochorionic monoamniotic twin pregnancy, the literature on its diagnosis and management was reviewed by electronic search in the Medline, OVID, Cochrane and PubMed databases between 1966 and 2019. The keywords used in the inquiry were: pregnancy, twins, monoamniotic, cord entanglement. There is a high risk of sudden fetal death in monoamniotic twins caused by entanglement of the umbilical cords, so timely diagnosis of chorionicity and amnionicity in twin pregnancy by ultrasonography may provide guidance for close fetal surveillance and thus improve obstetric outcome.